2019
DOI: 10.1021/acs.energyfuels.9b03132
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Water Utility Lime Sludge for Flue Gas Desulfurization in Coal-Fired Power Plants: Part III. Testing at a Higher Scale and Assessment of Selected Potential Operational Issues

Abstract: The feasibility of lime sludge utilization for flue gas desulfurization was evaluated by continuing the previous laboratory-scale studies at a higher scale and investigating two potential operational issues, namely viscosity and metal corrosion. Two lime sludge samples and a baseline limestone sample, which were previously characterized and tested for SO 2 capture from a simulated flue gas at a laboratory scale, were first tested at a 10-fold scale with a simulated flue gas, and then tested with a slipstream o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Wear removed the passivation film from the surface and destroyed the cementite network, resulting in subsurface cracks and deformable hardening, which exacerbated the corrosion. Aiming et al 23 studied wear and corrosion in the pump and found that uniform corrosion and wear occurred in areas below the critical speed value, resulting in slight quality loss. The region where the speed was higher than the critical value was the region of nonuniform tribocorrosion, and the mass loss increased sharply with a rise in speed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wear removed the passivation film from the surface and destroyed the cementite network, resulting in subsurface cracks and deformable hardening, which exacerbated the corrosion. Aiming et al 23 studied wear and corrosion in the pump and found that uniform corrosion and wear occurred in areas below the critical speed value, resulting in slight quality loss. The region where the speed was higher than the critical value was the region of nonuniform tribocorrosion, and the mass loss increased sharply with a rise in speed.…”
Section: Introductionmentioning
confidence: 99%
“…Dastgheib et al conducted a feasibility test evaluation on flue gas desulfurization of lime sludge. The corrosion resistances of carbon steel and stainless steel under various conditions were tested, and the results indicated that the corrosion resistance of stainless steel in the limestone slurry was obviously better than that of carbon steel.…”
Section: Introductionmentioning
confidence: 99%